The Anterolateral Ligament: An Anatomic Study on Sex-Based Differences. Issue 2 (22nd February 2017) - Daggett, Matt; Helito, Camilo; Cullen, Matthew; Ockuly, Andrew; Busch, Kyle; Granite, Joseph; Wright, Barth; Sonnery-Cottet, Bertrand
Background: The anterolateral ligament (ALL) has been shown to have an important role in rotatory stability of the knee. While there is abundant research on sex-based differences related to anterior cruciate ligament (ACL) rupture, there is a paucity of literature related to such differences in the ALL. Purpose: To define any sex-based differences in the ALL with regard to length, width, and thickness. Study Design: Descriptive laboratory study. Methods: The ALL was initially evaluated in 165 unpaired knees (92 males and 65 females after exclusion criteria applied). The length, width, and thickness of the ALL were measured using a digital caliper. Width and thickness were measured at the joint line just superior to the lateral meniscus. The Mann-Whitney test and Student t tests were used to compare measurements between males and females. The Pearson product-moment correlation was subsequently used to determine the correlation between height and weight and the statistically different morphometric variables. Results: The mean (±SD) thickness of the ALL in males was 2.09 ± 0.56 mm, almost twice as thick as females (1.05 ± 0.49 mm; P = 8.8 × 10 −20 ). There was also a statistically significant difference in ALL length ( P = 3.8 × 10 −7 ), but no significant difference was found for width. A moderate association was found between donor height and ALL thickness and length. Conclusion: The anatomic measurements of the ALL demonstrate a difference between sexes, and the ALL is significantly thicker in males than females. Clinical Relevance: As the role of the ALL in rotatory stability of the knee becomes better understood, the difference in the thickness of the ALL we have found between the sexes may be another factor why female athletes have an increased incidence of ACL rupture compared with males. This may also help explain why females have issues with knee laxity and rotatory instability.